QUILLBOT-ASSISTED COLLABORATIVE WRITING: IMPACT ON EFL STUDENTS’ DESCRIPTIVE WRITING AND SELF-EFFICACY - Fendi Sebastian Pramudiharjo; Ekaning Dewanti Laksmi; Niamika El Khoiri (Universitas Muhammadiyah Metro, 2025)
This study investigates how QuillBot-assisted Collaborative Writing affects EFL students' descriptive writing performance and self-efficacy. Employing a quasi-experimental design, 45 Indonesian senior high school students were divided into control (21 students) and experimental groups (24 students). The experimental group engaged in collaborative writing with QuillBot, while the control group followed a conventional teacher-centered approach. Data collection included pre-test and post-test writing assessments and a self-efficacy questionnaire. Mann-Whitney U test was applied to analyze the data due to violations of normality and homogeneity assumptions. The result revealed a significant difference in post-test scores between the groups. Meanwhile, self-efficacy showed no statistically significant influence on writing performance. These findings suggest that QuillBot-assisted Collaborative Writing enhances students’ interaction and writing proficiency. The use of QuillBot provides timely feedback and reduces the teachers’ load. Future research should explore long-term effects, student engagement levels in the areas of cognitive, behavior, social, and affective engagement, and qualitative perspectives on AI-assisted writing in K-12 setting. This research contributes to the growing discussion related to QuillBot’s roles in language learning, emphasizing its abilities as a complementary rather than autonomous instructional tool.